Acne vulgaris in 28 yo woman with PCOS: A CASE REPORT - Ferent Virginia Kaligis; Saskia Amadea Yonathan; Katherine Marcella; Andrew Laurie Bustaman; Iqbal Ibrahim; Peter Nugraha (Medical Clinical Update, 2023)
Acne vulgaris is distinguished by a combination of inflammatory and non-inflammatory skinblemishes that appear in the form of patches of various varieties emerge, commonly at the sametime. Acne causes severe morbidity, including scarring and psychological disorders such as poorself-image, sadness, and anxiety, which negatively impact the quality of life. Those consequencescan be prevented with early treatment. This case report aims to demonstrate the treatment ofacne vulgaris.